Primary care givers’ experiences of family centred care in a paediatric hospital in Gauteng - Mashishi, Pretty (My University, 2022)
Family Centred Care (FCC) is an approach to the planning, delivery and evaluation of health care that is grounded in a mutually beneficial partnership among patients, families and health care professionals (Johnson and Abraham, 2012). When nursing patients their loved ones are involved and a holistic approach is applied. The benefits of FCC are well documented and include shorter hospital stays, improved preparedness for discharge and less emotional stress for both families and patients (Johns Hopkins Children’s Center, 2018).Most nurses acknowledge the importance of FCC and are practising it to some extent however, unsuccessful implementations of FCC are known to exist in various clinical practice settings (Almaze and De Beer, 2017). The experiences of Primary Care Givers (PCGs) in paediatric care are important to understand because according to Hill, Knafl, and Santacroce, 2018 parents are the voice, advocates and care givers for their children including during critical paediatric illness (Hill et al., 2018). Therefore, it is important to know what families actually need as opposed to what healthcare professionals assume they need (Jordan, 2018). The purpose of this research was to determine the primary care givers experience of Family Centred Care in a paediatric hospital in Gauteng. Knowing the positive and negative experiences of FCC by PCGs assists health care providers to gain insight into how to involve PCGs and improve the practice of FCC. A sample of participants was selected using purposeful sampling from Primary Care Givers who were lodging at the hospital. A qualitative descriptive design was used in this research. Interviews with semi-structured questions were used to collect data. Questions were based on four key elements of FCC, as identified by Conway et al(2006) and were used as a template design for the questions. Data was analysed using a latent content analysis approach. The findings were described using themes formed from the interview questions in relation to the core concepts of FCC. The findings of this study reveal that primary caregivers encounter both positive and negative experiences when core concepts of FCC are implemented. Regarding participation, primary caregivers are willing to engage in care with health care professionals as the enabling factor. Respect and dignity are primarily conveyed through human and professional courtesies. These professional and friendly courtesies also facilitate information sharing. The severity of the condition of a child is a key limiting factor for participation but primary caregivers place trust in the knowledge of health care professionals. PCGs place total trust in the knowledge of health care providers.Collaboration was not present in terms of the Institute for Patient and Family-Centred Care (IPFCC) definition as there was no evidence of involvement in policy and program development. Recommendations Health care professionals must be acquainted with the core concepts of FCC and how their actions can impact the experiences of primary caregivers through efforts to act professionally and kindly so that the care environment is conducive for primary caregivers. It is also recommended to educate primary caregivers regarding coping with their hospitalised child and also regarding FCC. Finally, the hospital should develop policies for FCC regarding training, implementation and regular evaluation.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022